The Value of Fitrah And Its Relationship With Islamic Education - Harahap, Mhd. Harmidi; Tengku Kasim, Tengku Sarina Aini Binti; Yussuf, Ahmad Bin (Journal Analytica Islamica, 2024)
The purpose of this study is to explore further the meaning of fitrah and its relationship with Islamic education. As in many references, the concept of fitrah is an innate natural thing inherent in human beings brought from birth. Fitrah means the potential possessed by humans. The potential will have a positive impact on human development if developed through the process of Islamic education. This study uses a qualitative method of library research. The results of this study indicate that humans are born with different potentials. There is potential for good and there is also potential for bad. This potential will later develop into its power which, if managed properly, will be able to produce civilization through a good educational process. The goal of Islamic education should be to educate to face Islam, meaning that Islamic education is directed so that students are more inclined to the teachings of Islam. At the same time, fitrah also means that Islamic education serves to know the nature of God and at the same time know himself. By using a literature approach, through the review of authoritative books and journals, this paper will try to take a comprehensive look at the discourse of the term fitrah in terms of language, the meaning of the Qur'an and Hadith, fitrah in the view of philosophy and psychology.Tujuan penelitian ini adalah untuk menggali lebih jauh makna fitrah dan hubungannya dengan pendidikan Islam. Seperti dalam banyak referensi, konsep fitrah merupakan suatu hal kodrati yang melekat pada diri manusia yang dibawa sejak lahir. Fitrah artinya potensi yang dimiliki manusia. Potensi tersebut akan memberikan dampak positif bagi pembangunan manusia jika dikembangkan melalui proses pendidikan Islam. Penelitian ini menggunakan metode kualitatif penelitian kepustakaan. Hasil penelitian ini menunjukkan bahwa manusia dilahirkan dengan potensi yang berbeda-beda. Ada potensi baik dan ada juga potensi buruk. Potensi tersebut nantinya akan berkembang menjadi kekuatannya yang apabila dikelola dengan baik akan mampu melahirkan peradaban melalui proses pendidikan yang baik. Tujuan pendidikan Islam hendaknya mendidik untuk menghadapi Islam, artinya pendidikan Islam diarahkan agar peserta didik lebih condong pada ajaran Islam. Pada saat yang sama, fitrah juga berarti pendidikan Islam berfungsi untuk mengetahui hakikat Tuhan sekaligus mengenal diri sendiri. Dengan menggunakan pendekatan kepustakaan, melalui telaah buku dan jurnal otoritatif, tulisan ini akan mencoba melihat secara komprehensif wacana istilah fitrah dari segi bahasa, makna Al-Qur'an dan Hadits, fitrah dalam pandangan dari filsafat dan psikologi.